'Striving for normality' when coping with Parkinson's disease in everyday life: A metasynthesis. (June 2021) - Haahr, Anita; Groos, Hannah; Sørensen, Dorthe
Abstract: Background: Parkinson's disease is a chronic, progressive neurodegenerative disease which affects more than ten million people worldwide. Living with Parkinson's disease has a high impact on everyday life, and may affect quality of life negatively. Individualized coping strategies are needed to deal with the disease on a daily basis and still enjoy a social life. Objective: The aim of this study was to identify and describe strategies for coping adopted by individuals living with Parkinson's disease in their daily lives. Design: The study is designed as a meta-ethnographic metasynthesis and follows Sandelowski and Barroso's guidelines for synthesizing qualitative research. Datasources: Based on an exhaustive literature search in the following databases: CINAHL, MEDLINE, PsychINFO, Scopus and Swemed, as well as Mednar, parkinson.org, Google Scholar and OpenGrey, with no limit on the search date, 14 articles were included. Review methods: The data were analyzed through a taxonomic and inductive analysis focusing on coping with Parkinson's disease in daily life. Results: The findings revealed that the overarching motivation for patients to cope with Parkinson's disease was maintaining normality and preserving the self. The coping strategies used were: Staying independent, Focusing on the present and Avoiding challenging situations. Conclusions: Coping with Parkinson's disease is an ongoing and complex process of balancing the strategies used, while holding on to the 'self' that pre-dated Parkinson's disease, and at the same time adjusting one's identity to embrace living with a chronic condition. In this process, optimism and positive thinking would seem to be very fruitful. Further, the synthesis revealed that relatives often act as informal caregivers and hence as an important support in daily life. Healthcare professionals must know about coping strategies in order better to support the patients.